Acute AMPK Activation Does Not Adequately Stimulate Insulin Signaling in Skeletal Muscle Models of Myotonic Dystrophy Type 1 - Adjei-Afriyie, Yaw Ofosu (Université d'Ottawa / University of Ottawa, 2026)
Myotonic Dystrophy Type 1 (DM1) is a multisystemic neuromuscular disease characterized by skeletal muscle weakness, muscle atrophy, and myotonia. However, patients often also experience cognitive impairments, gastrointestinal complications, and insulin resistance. Insulin resistance exacerbates muscle weakness and atrophy in DM1, but its pathomechanism has not been adequately described in the context of DM1. The aim of this study is to characterize the molecular mechanisms of insulin resistance in DM1 and how AMPK stimulation can impact insulin signaling. My first aim analyzes proteomic data from sedentary wildtype, sedentary HSA-LR, and exercised HSA-LR mice to detect and predict dysregulated proteins in insulin and exercise molecular pathways. My second aim examines molecular interactions impacting GLUT4 translocation in the HSA-LR mouse model after acute AMPK stimulation. My final aim examines molecular interactions impacting GLUT4 translocation in a DM1 myotube model after insulin and AMPK stimulation. Proteomic analysis predicted that exercise significantly upregulates PGC-1α, a transcription coactivator integral to metabolic regulation. When AMPK, an upstream regulator to PGC-1α, is targeted in HSA-LR mice and DM1 myotubes with AICAR, there is no improvement in the AKT-AS160 insulin signaling axis. Our findings confirm insulin resistance in DM1 and demonstrates an impaired response to acute AMPK stimulation.
Keywords: Myotonic dystrophy type 1 (DM1); exercise; insulin; AMPK; PGC-1α; Akt; AS160; GLUT4